SPD-Parteitag 1968 in Nürnberg; 17.03.1968 - 21.03.1968 (2008)
2. Verhandlungstag am 18.03.1968:<NZ>Generaldebatte:<NZ>Alfred Schulz, Protokoll Seiten 216 - 218, 00'01'' - 05'45'';<NZ>Horst Ehmke, Protokoll Seiten 218 - 220, 06'14'' - 11'57'';<NZ>Hans-Jürgen Wischnewski, Protokoll Seiten 220 - 223, 12'12'' - 21'42'';<NZ>Reinhard Scholz, Protokoll Seiten 223 - 224, 21'55'' - 24'16'';<NZ>Karl Schiller, Protokoll Seiten 224 - 227, 24'38'' - 39'25'';<NZ>Karl Eggers, Protokoll Seiten 227 - 228, 39'34'' - 40'23'';<NZ>Annemarie Renger, Vorsitzende, Protokoll Seite 228, 40'25'' - 41'18'';<NZ>Willi Brundert, Protokoll Seiten 228 - 230, 41'23'' - 49'30'';<NZ>Rudolf Kaffka, Protokoll Seiten 230 - 231, 49'45'' - 51'57'';<NZ>Willi Michels, Protokoll Seiten 231 - 234, 52'08'' - 60'02''.; Bemerkungen: Fortsetzung von CD-R 407